TRANSLATION METHODS APPLIED IN TRANSLATING QUOTATIONS IN “THE SECRET” BY RHONDA - FEBRIANTI, VICKY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Translation Methods, The Secret, Quotations.Translation helps human to get information written in any language evenwhen it is written in foreign languages. Therefore translation happens in printed media. Books have been popular printed media. The Secret written by Rhonda Byrne is a popular self-help book which has been translated into 50 languages including Indonesian (“The Secret”, n.d., para.5-6).This study is meant to find out the translation methods applied in The Secret. The writer uses a theory proposed by Newmark (1988) which classifies translation methods into eight types.The study used document analysis of qualitative approach because the data are from a textbook. The data are quotations containing interrogative sentences oftwenty four teachers written in The Secret.The writer found seven quotations using semantic translation and 14 quotations using communicative translation. The method which is mostly applied is communicative translation. The findings lead the writer to infer that since the data are originally from spoken discourse, the translator thought that communicative translation produces a translation that is easily understood by the readers.The writer suggests the next researchers conduct research about translationmethods used in written discourses which may result in findings different from the study on spoken discourses.